The Empirical Study for the Impact on Integration of Industry and Education Values in Higher Vocational Education on Career Planning of Students - Yi, Hongling; lihjen, Jew (Journal of Roi Kaensarn Academi, 2024)
Background: This research endeavor delves into the implications of integrating industry and education values within higher vocational education frameworks on students' career planning prowess. It seeks to unravel the complex interplay between institutional support and various integration modalities in shaping vocational education outcomes. Aims: By examining these dynamics, the study aims to furnish both theoretical underpinnings and practical recommendations for advancing vocational education reforms, with a focus on enhancing students' career readiness and holistic development. Methodology: Utilizing a survey-based approach coupled with rigorous quantitative analyses, including the Schein Career Values Inventory and Maslow's Hierarchy of Needs Assessment Scale, we amassed data from a representative sample of 1,082 students across five leading higher vocational colleges in Guangdong Province. Comprehensive statistical techniques, encompassing descriptive statistics, correlation and regression analyses, and structural equation modeling, were employed to test our hypotheses and elucidate the intricate mechanisms linking industry-education integration to career planning competencies. Results: Our findings underscore the profound positive effect of integrating industry and education values on students' career planning abilities. Notably, school support emerges as a pivotal mediator in this relationship, highlighting the crucial role of educational resources and career guidance services in fostering students' career trajectories. Furthermore, the study reveals that the mode of integration significantly moderates this relationship, with the school-enterprise cooperation model notably amplifying the beneficial impacts of industry-education integration on career planning. Conclusion: These insights underscore how the alignment of vocational training with industry needs fosters skills development and employment prospects, thereby bolstering students' career planning acumen. The pivotal roles played by institutional support and integration modalities in this process are emphasized. Consequently, we advocate for heightened industry-education collaboration, optimized school support systems, and curricula tailored to market demands as essential strategies for advancing students' holistic development and career readiness within higher vocational education settings.